Richemont, The Right Choice: Case Study for Effective Creation of Mobile Learning - Sazen, Noorie (International Journal of Advanced Corporate Learning (iJAC), 2020)
This is a case study detailing the solution developed by Saffron Interactive for Richemont International to support their learning requirements around information security.